PENGARUH ADMINISTRASI PENDIDIKAN TERHADAP KINERJA GURU MADRASAH BINTAN - Khrisfison, Khrisfison (FASTABIQ: JURNAL STUDI ISLAM, 2023)
Education administration is basically an effort to improve and improve the quality of education, including through improving teacher performance. However, in a limited way, administration is seen as complicating the duties of teachers in carrying out their duties and functions. This study aims to determine the effect of education administration on teacher performance at MTs Negeri Bintan. The population in this study were 31 teachers. Sampling used the saturated sample or census method, meaning that all members of the population were used as samples, namely 31 teachers. Sources of data are primary data and secondary data, while data collection techniques use questionnaires or questionnaires. Analysis of the data used is the test instrument and test the hypothesis by using a simple linear regression analysis equation. The results of this study are that education administration has a significant and positive effect on teacher performance at MTs Negeri Bintan. A significant positive correlation value means that the better the administration of education, the better or increase the performance of teachers at MTs Negeri Bintan, and vice versa. There is a very strong influence or relationship between educational administration variables on teacher performance. Then the contribution of education administration in influencing teacher performance is 76%. while the remaining 34% is influenced by other variables outside the research or other factors not examined in this study. The results of this study confirm the opinion that proper administrative placement will help the quality of education through better teacher performance.Keywords: educational administration; teacher performance; madrasas